Undisciplining Teaching. Reflections on a Shared Philosophical-Pedagogical Experience - Cerletti, Alejandro (2018)
This paper addresses the question of the "Teaching of Philosophy," elucidating, in particular, the possibility of a "Philosophical Teaching of Philosophy" focused, fundamentally, on conceptual creation rather than on the repetition or transfer of some canonical, philosophical knowledge, from teachers to their students. Therefore, the originality of thinking is privileged rather than the repetition of some recipes to learn. As a display of the proposed ideas, some philosophical teaching and learning experiences are described, which are intended to be consistent with these ideas.